Arthropod and Disease Management in Boxwood Production. Issue 1 (7th June 2022) - Dhakal, Kripa; Bika, Ravi; Ghimire, Bhawana; Parajuli, Madhav; Neupane, Sandhya; Neupane, Krishna; Addesso, Karla M; Baysal-Gurel, Fulya
Abstract: Boxwood ( Buxus spp.) is the most commonly cultivated woody ornamental shrubs in landscape settings and nursery production. Boxwood is grown for its attractive evergreen foliage and versatility in both formal and informal gardens. Meeting the high demand for boxwood plants worldwide has become challenging in recent years as the boxwood industry has been negatively impacted by a growing number of serious diseases and arthropod pests. Globally, the most common arthropods of concern are boxwood leafminer (Monarthropalpus flavus, Diptera: Cecidomyiidae), boxwood psyllid (Psylla buxi; Hemiptera; Psyllidae), Eurytetranychus buxi (Acari: Tetranychidae) and the invasive moth, Cydalima perspectalis (Lepidoptera: Crambidae). Moreover, major diseases of boxwood include boxwood blight ( Calonectria pseudonaviculata, Hypocreales: Nectriaceae), Volutella blight ( Pseudonectria buxi, Hypocreales: Nectriaceae), and Phytophthora root and crown rot ( Phytophthora spp., Peronosporales: Peronosporaceae). These pests and diseases can lead to significant economic losses to growers and can decimate plants in landscape settings. Here we have reviewed recent research advances focused on the description and management of boxwood arthropod pests and diseases. Boxwood arthropod pests and diseases can be managed by implementing integrated arthropod pest and disease management strategies such as sanitary and cultural practices, genetic resistant cultivars, biological and chemical control methods. This information is provided to aid nursery producers, landscape industry professionals, and other stakeholders in developing integrated arthropod pest and disease management plans for boxwood.